An enantioselective aza-Henry reaction of trifluoromethyl ketimines catalyzed by phase-transfer catalysts. Issue 18 (9th August 2019) - Wang, Xiaonan; Gao, Yuan; Wei, Zhonglin; Cao, Jungang; Liang, Dapeng; Lin, Yingjie; Duan, Haifeng
Abstract : An enantioselective aza-Henry reaction of acyclic trifluoromethyl ketimines was performed using a bifunctional catalyst. The products were converted to diamines and imidazolidine-2-ones. Abstract : An efficient enantioselective aza-Henry reaction of acyclic trifluoromethyl-substituted ketimines has been performed successfully by using a bifunctional chiral ammonium catalyst bearing multiple H-bonding donors, which was derived from quinine. The corresponding products were obtained in excellent yields (up to 98% yield) with high enantioselectivities (up to 96% ee), and they could be easily converted to diamines and imidazolidine-2-ones with chiral tetrasubstituted carbon centers in excellent yields with high enantioselectivities.